Pemrograman Linier Metode Simpleks untuk Optimalisasi Keuntungan Produksi Industri Piscok - Palahudin Palahudin; Suci Rahmawati; Kamelia Agnesta; Rina Erlita; Yusuf Andika Rachmat; Insan Saputra (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Piscok production in Indonesia is experiencing significant growth, but there are challenges in terms of efficiency. The purpose of this study is to maximize the profit of piscok production through linear programming with the simplex method. This research analyzes data to find the most effective production combination, given issues such as raw materials and production capacity. The analysis results show that by producing four units of Cheese Piscok and ten units of Bluberry Piscok, the maximum profit that can be achieved is Rp38,000. This research adds insight to small and medium industry players about the application of linear programming in the food sector.